Characterization and quantification of alcohol‐related polyneuropathy by magnetic resonance neurography. (11th October 2021) - Rother, Christian; Bumb, Jan Malte; Weiler, Markus; Brault, Anna; Sam, Georges; Hayes, John M.; Pietsch, Adriana; Karimian‐Jazi, Kianush; Jende, Johann M. E.; Heiland, Sabine; Kiefer, Falk; Bendszus, Martin; et al.
Abstract: Background: We characterized and quantified peripheral nerve damage in alcohol‐dependent patients (ADP) by magnetic resonance neurography (MRN) in correlation with clinical and electrophysiologic findings. Methods: Thirty‐one adult patients with a history of excessive alcohol consumption and age‐/sex‐matched healthy controls were prospectively examined. After detailed neurologic and electrophysiologic testing, the patient group was subdivided into ADP with alcohol‐related polyneuropathy (ALN) and without ALN (Non‐ALN). 3T MRN with anatomical coverage from the proximal thigh down to the tibiotalar joint was performed using dual‐echo 2‐dimensional relaxometry sequences with spectral fat saturation. Detailed quantification of nerve injury by morphometric (cross‐sectional area [CSA]) and microstructural MRN markers (proton spin density [ρ], apparent T2‐relaxation‐time [T2app ]) was conducted in all study participants. Results: MRN detected nerve damage in ADP with and without ALN. A proximal‐to‐distal gradient was identified for nerve T2‐weighted (T2w)‐signal and T2app in ADP, indicating a proximal predominance of nerve lesions. While all MRN markers differentiated significantly between ADP and controls, microstructural markers were able to additionally differentiate between subgroups: tibial nerve ρ at thigh level was increased in ALN ( p  < 0.0001) and in Non‐ALN ( p  = 0.0052) versus controls, and T2app was higher in ALN versus controls ( p  < 0.0001) and also in ALN versus Non‐ALN ( p  = 0.0214). T2w‐signal and CSA were only higher in ALN versus controls. Conclusions: MRN detects and quantifies peripheral nerve damage in ADP in vivo even in the absence of clinically overt ALN. Microstructural markers (T2app, ρ) are most suitable for differentiating between ADP with and without manifest ALN, and may help to elucidate the underlying pathomechanism in ALN. Abstract : We characterized and quantified peripheral nerve damage in 31 adult alcohol‐dependent patients in comparison with 20 healthy age‐ and sex‐matched controls by applying high‐resolution magnetic resonance neurography (MRN) in correlation with clinical and electrophysiologic findings. MRN detected nerve damage in alcohol‐dependent patients in vivo with a proximal‐to‐distal gradient, indicating a predominance of nerve lesions at thigh level, and even in the absence of a clinically overt alcoholic polyneuropathy. The quantitative, microstructural MRN markers proton spin density and apparent T2‐relaxation time were most suitable for differentiating between alcohol‐dependent patients with and without alcoholic polyneuropathy, and may help to better understand the underlying pathomechanism in alcoholic polyneuropathy.